Perancangan Sistem Informasi Pendaftaran Waralaba (Franchise) Pada PT. Oppa Oppa Tokpokki - Fahmi Taqiudin; Rinna Rachmatika (CV. Multi Kreasi Media, 2023)
The rapid development of information technology today has a very important role to achieve goals in a company. Information systems are media that are quite helpful in business processes such as processing data so that it is more effective. PT. Oppa Oppa Tokpokki is a business engaged in korean streetfood food and opens opportunities for anyone who wants to become a partner with the franchise system. In the registration and information in detail still using Whatsapp and Instagram media, so admins take longer to process registration. To help and provide solutions in the above problems, a franchise registration information system was created at PT. Oppa Oppa Tokpokki. This system presents information about the company and there are features for registering to be partners, logins, logout, payment and payment confirmation. This system has been functional testing using the blcakbox testing method with valid results throughout the test..